2019
DOI: 10.5114/aoms.2019.87274
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0017728 as an oncogene in gastric cancer by sponging miR-149 and modulating the IL-6/STAT3 pathway

Abstract: Introduction: Circular RNAs (circRNAs) have been identified as competing endogenous RNAs (ceRNAs) to mediate gene expression participating in the progression of multiple cancers, including gastric carcinoma (GC). However, the underlying molecular mechanisms by which circRNAs-modulated cell proliferation and apoptosis in GC had not been completely clarified. In our study, hsa_ circ_0017728 as a potential oncogene competing endogenous RNA (ceRNA) was investigated in the progression and development of gastric car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…They can also act as templates for protein translation and mediate immune responses [ 7 , 8 ]. Dysregulation in their role as miRNA-sponge has been reported in several types of gastrointestinal malignancies, including hepatocellular carcinoma [ 9 , 10 , 11 ], pancreatic [ 10 , 12 ], colorectal [ 10 , 11 , 13 ] and gastric cancer [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can also act as templates for protein translation and mediate immune responses [ 7 , 8 ]. Dysregulation in their role as miRNA-sponge has been reported in several types of gastrointestinal malignancies, including hepatocellular carcinoma [ 9 , 10 , 11 ], pancreatic [ 10 , 12 ], colorectal [ 10 , 11 , 13 ] and gastric cancer [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ,…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have demonstrated the role of circRNAs as miRNA-sponges in GC [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. For example, it has been shown that alterations in circLARP4/miR-424/LATS1 [ ...…”
Section: Introductionmentioning
confidence: 99%